2018
DOI: 10.1002/cssc.201702342
|View full text |Cite
|
Sign up to set email alerts
|

Design of Copper‐Based Bimetallic Nanoparticles for Carbon Dioxide Adsorption and Activation

Abstract: Cu-based nanoparticles (NPs) are promising candidates for the catalytic hydrogenation of CO to useful chemicals because of their low cost. However, CO adsorption and activation on Cu is not feasible. In this work we demonstrate a computational framework that identifies Cu-based bimetallic NPs able to adsorb and activate CO based on DFT calculations. We screen a series of heteroatoms on Cu-based NPs based on their preference to occupy a surface site on the NP and to adsorb and activate CO . We revealed two desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…On metallic surfaces, CO 2 activation usually consists of electronic charge transfer from the metal to CO 2 . [108][109][110] On metal oxides, on the other hand, the adsorption exploits the amphoteric nature of CO 2 , which has a partial positive charge on the C atom (+0.37 e from Mulliken's population analysis) and negative charges on the two O atoms (−0.18 e). 40 During the adsorption, the electron-deficient C atom and the more electron-rich O atoms can be attacked by either electron-rich or electron-deficient active sites, respectively.…”
Section: Catalysis Science and Technologymentioning
confidence: 99%
See 4 more Smart Citations
“…On metallic surfaces, CO 2 activation usually consists of electronic charge transfer from the metal to CO 2 . [108][109][110] On metal oxides, on the other hand, the adsorption exploits the amphoteric nature of CO 2 , which has a partial positive charge on the C atom (+0.37 e from Mulliken's population analysis) and negative charges on the two O atoms (−0.18 e). 40 During the adsorption, the electron-deficient C atom and the more electron-rich O atoms can be attacked by either electron-rich or electron-deficient active sites, respectively.…”
Section: Catalysis Science and Technologymentioning
confidence: 99%
“…109 Moreover, they showed that Zr sites can be oxidized because of their high oxophilicity; however, they are still able to adsorb and activate CO 2 easily. 110 Dixit et al 111 The adsorption configuration of CO* 2 changes with the structure and composition of the catalyst surface. 99,[108][109][110][111][112][113][114] Usually, the C atom and one O atom of CO* 2 bind to one or two metal atoms [108][109][110]112 (on the "top" or "bridge" adsorption sites).…”
Section: Catalysis Science and Technologymentioning
confidence: 99%
See 3 more Smart Citations